(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article addresses the challenge of differentiating dental diseases with similar clinical signs, using periodontitis as an example. Symptomatic similarities between periodontitis, pulpitis, endodontic-periodontal diseases, and gingival hypoplasia often complicate diagnosis. The article analyzes the possibilities of accurate and precise diagnosis using modern diagnostic methods such as clinical examination, X-rays, CBCT, thermotesting, and others[12]. The importance of differential diagnosis for distinguishing diseases and ensuring effective treatment is emphasized.